Prosthesis-patient mismatch as a predictor of accelerated structural dysfunction of biological aortic valve prostheses - G. G. Khubulava; Z. O. Maliev; N. N. Shikhverdiev; A. I. Lyubimov; D. I. Ushakov (Вестник хирургии имени И.И. Грекова, 2022)
OBJECTIVE. Identification of predictors of dysfunction of biological aortic valve prostheses in the long-term period after surgical treatment.METHODS AND MATERIALS. We analyzed the completed treatment cases for the period from 2015 to 2020 and echocardiography data of 74 patients (42 men and 32 women) with an average age of 67.0±4.2 years with bioprostheses implanted in the aortic position. The average follow-up period was 4 years. The transaortic flow velocity, the average and peak transvalvular gradients, the area of the effective opening of the prosthesis, the myocardium mass index, the thickness and mobility of the cusp of the biovalve were evaluated. The presence of the pronounced PPM in a patient was determined at iEOA values less than 0.65 cm2/m2, moderate - at values from 0.65 to 0.85 cm2/m2, mild - up to 0.85 cm2/m2.RESULTS. PPM was recorded in 27% of cases. Structural dysfunction was observed in 12.5% of cases, it mainly included stenosis of the bioprosthesis (10%). In 2.5% of cases, reintervention was performed for severe stenosis of the AV bioprosthesis. During the multifactorial analysis, we revealed that PPM was a predictor of the development of structural dysfunction of aortic valve bioprostheses in the long-term period after surgery (p<0.005).